Assessing the 3D structural behavior of RC library buildings with/without non-structural elements considering shake table tests and 3D numerical analyses - Karalar, Memduh; Çavuşlu, Murat; Ozturk, Hakan; Mert, Necati; Ahmad, Mahmood; Sabri, Mohanad Muayad Sabri (Frontiers in Materials, 2022)
In this study, it is aimed to reveal how anchored and unanchored non-structural elements (NEs) in reinforcement concrete (RC) library structures change the earthquake behaviors of these structures. A library structure is selected for three-dimensional (3D) analysis. First, seismic shake table tests are performed for selected NEs modeled with/without anchorage to the structure. Owing to these seismic tests, the largest seismic displacement values that occurred during 10 different earthquakes on each anchored and unanchored NE are acquired. Then, special seismic loads (e.g., high bookcase loads and heavy table loads) of anchored and unanchored NEs are calculated, taking into account the ASCE/SEI 7-16 seismic design code and the 2018 Turkish Building Earthquake Code (TBEC). Seismic spring values of NEs are calculated using the obtained seismic forces and maximum seismic displacements for the NEs. Then, these spring values are applied to the base of the NEs in the 3D model of the structure, and 10 different earthquake analyses are conducted for the library structures with anchored and unanchored NEs. According to the numerical results, the seismic effects of NEs on the earthquake behavior of RC library structures are evaluated for two different seismic design codes in detail, and it is concluded that NEs should not be neglected while modeling and analyzing RC library structures. It is seen from the seismic analyses that for the TBEC, 37, 56, and 126 mm maximum seismic displacements are observed on the library structure for structures without NEs, structures with unanchored NEs, and structures with anchored NEs, respectively. Moreover, for the ASCE code, 32, 45, and 119 mm maximum displacements are seen on the library structure for structures without NEs, structures with unanchored NEs, and structures with anchored NEs, respectively. It is clearly understood that anchored or unanchored NEs have different seismic effects on the 3D earthquake behavior of library structures.